Efektivitas Penggunaan Media Courselab Dalam Meningkatkan Hasil Belajar Matematika Siswa - Rizka Rizka; Muhazzab Said; Irma T (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2016)
Courselab can be able to make the lessons more varied and fun, so that adds to the interest of students to participate in learning. This study aims to determine whether the use courselab effective in improving students' mathematics learning outcomes. This study is an experimental research conducted in class VIII MTs Guppi Tompe Luwu Utara. The samples are saturated sample consisting of all students of class VIII MTs Guppi Tompe consisting of two classes, namely class VIII A of 27 students (grade control) and VIII B class consisting of 22 students (experimental group). The instrument used is the achievement test. Descriptive analysis of pre-test the control class and experimental class was flat at 53.40 and 52.68. This means that both classes have the same level of learning outcomes. Meanwhile, the results of the descriptive analysis of post-test on the control and experimental classes are 55.55 and 76.77. Thus, it appears that the use of media courselab effective in improving learning outcomes math class VIII MTs Guppi Tompe.